PENYULUHAN HUKUM MENGENAI ISU KELUARGA DAN UMKM DI DESA SEMAWUNG - Budi Wibowo, Muhammad Kurniawan; Fajri, Aditya; Luqmanul Hakim; Muhammad Muchlis Hidayat (Jurnal Indonesia Mengabdi, 2025)
This research aims to increase the legal awareness of the Semawung Village community, particularly in terms of family law and legal issues faced by small business actors. Limited access to legal information and low legal literacy have led to many unresolved legal issues. Therefore, a legal counselling programme was held to provide education and legal assistance to the local community. This research employs a qualitative approach by analyzing visual documentation and literature studies. Data were collected through observations of counseling activities conducted by students in the Community Service Program (KKM). The findings indicate that legal counseling helps improve public awareness of their rights and obligations. Additionally, small business owners gained better knowledge of business legality, allowing them to operate more systematically. The discussion highlights that interactive counseling methods involving active community participation make legal materials easier to understand and apply. In conclusion, legal counseling programs are effective in increasing legal awareness. Continuous implementation of this program is necessary to ensure broader and long-term benefits.